Women in sports: the applicability of common national reference intervals for inflammatory and coagulation biomarkers (HemSter Study) - Radišić Biljak, Vanja (Array, 2021)
Introduction: Intensive physical activity causes functional and metabolic changes in the athlete"s organism. The study aimed to verify the commonnational available reference intervals (RIs) for common inflammatory and screening coagulation tests in a population of healthy young female athletes.Materials and methods: One hundred and twenty-one female athletes (age range: 16–34), from various sports disciplines (water polo, handball,volleyball, football, basketball), were included in the study. All participants completed the international physical activity short-form questionnaire.Blood samples were collected between 8–10 am, after an overnight fast, before any physical activity. Reference intervals were determined accordingto Clinical & Laboratory Standards Institute EP28-A3C Guidelines.Results: Calculated RIs for white blood cell count (WBC), prothrombin time (PT), and activated partial thromboplastin time (APTT) ratio were inaccordance with the common national RIs. Calculated RI for C-reactive protein (CRP) was lower (<2.9 mg/L) than the proposed cut-off for a healthypopulation (<5.0 mg/L). Reference interval for fibrinogen was higher (1.9–4.4 g/L), than the available RIs (1.8–3.5 g/L). D-dimer cut-off value wasset at 852 μg/L fibrinogen equivalent units (FEU), higher than the proposed 500 μg/L FEU for venous thromboembolism (VTE) exclusion.Conclusions: The applicability of the available RIs for WBC count, PT, and APTT-ratio was confirmed. However, RIs for CRP and fibrinogen differedsignificantly than the available common national RIs for the healthy non-athletes" population. A higher cut-off for D-dimers should be extensivelyverified before implementation for VTE diagnosis exclusion in a group of healthy young female athletes.